2016
DOI: 10.14689/ejer.2016.63.21
|View full text |Cite
|
Sign up to set email alerts
|

Training of Critical Thinking Skills in Teacher Candidates and Placebo Effect: A Quasi-Experimental Study

Abstract: Problem Statement: In recent years many different studies have examined critical thinking disposition; however, these studies focus on investigating the variables that are related to this subject. There are actually few empirical studies in the literature. It is clear that there is a need for experimental research in order to comprehend the process of critical thinking in-depth. Purpose of the Study:This study investigates the contrastive effect of an experimental program and the placebo effect on the improvem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 5 publications
1
10
0
3
Order By: Relevance
“…However, at the level of p<.05, no significant difference was particularly found, these proved that there is no significant difference in critical thinking towards gender. The findings of this study are correlation to the previous findings of Demirbag et al (2016); that is, there is no difference in critical thinking disposition total scores between male and female. According to Table 5, it shows that the different levels at university are disconnected with critical thinking disposition significantly.…”
Section: Critical Thinking Dispositionsupporting
confidence: 89%
“…However, at the level of p<.05, no significant difference was particularly found, these proved that there is no significant difference in critical thinking towards gender. The findings of this study are correlation to the previous findings of Demirbag et al (2016); that is, there is no difference in critical thinking disposition total scores between male and female. According to Table 5, it shows that the different levels at university are disconnected with critical thinking disposition significantly.…”
Section: Critical Thinking Dispositionsupporting
confidence: 89%
“…A number of studies showed different results about the influence of demography on students' critical thinking skill. There were some studies pinpointing that demographical aspect did not significantly influence students' critical thinking skill (Demirbag, Unisen, & Yesilyurt, 2016). In addition, other study revealed that demography had significantly influenced students' critical thinking skill (Harish, 2013).…”
Section: Treatmentsmentioning
confidence: 99%
“…Grossman, Hammerness and McDonald (2009) discovered that teaching practice was a challenging task for prospective teachers. Moreover, the realities of classroom and expectations of prospective teachers have an apparent clash (Demirbag, Ünişen, & Yesilyurt, 2016).…”
Section: Introductionmentioning
confidence: 99%